La función de la orientación al ergativo en el discurso narrativo Malecu - Krohn, Haakon Stensrud (2014)
This paper analyzes the use of the so-called ergative orientation in traditional narrative discourse in Maleku, both quantitatively and qualitatively, within the functionalist framework. The analyses indicate that this construction can be explained as a device principally used to avoid the possible ambiguity regarding the grammatical case of the nominal phrases that codify the ergative participants.